PENGARUH TERAPI BEKAM TERHADAP KADAR GULA DARAH PADA PASIEN BEKAM DI KLINIK TERAPI BEKAM DR. ABDURRAHMAN KOTA MEDAN - HAFIZ AZMI; EKA AIRLANGGA (JURNAL ILMIAH SIMANTEK, 2021)
Cupping therapy is a method that has been known for a long time, especially by dry and wet cupping. Considered to helpdecrease blood levels. To study the effect of therapy on blood sugar levels. Purpose of the study: to determine the effect ofcupping therapy on blood sugar levels at the cupping therapy clinic dr. Abdurrahman Medan City. The design of this studywas cross sectional by comparing pre-test and post-test scores in one group without comparison. The sample is determinedby purposive sampling with a total sample of 44 people. Analysis of the data used the paired T-test. Patients in the cuppingtherapy clinic dr. Abdurrahman Medan City is 26 men and 18 women with the most age range 31 - 40 years. Paired T-testresults showed that there was an effect of cupping therapy on blood sugar levels in cupping patients at the cupping therapyclinic dr. Abdurrahman Medan City with a value of p = 0.001 (<0.05). There is a significant effect between cupping therapy onchanges in blood sugar levels.